Strategi dan Hambatan Pedagang Kaki Lima Dalam Meningkatkan Penjualan ( Studi Kasus PKL di Telanaipura Kota Jambi) - Rafidah Rafidah (Indonesian Journal of Islamic Economics and Business, 2019)
This study aims to determine how the strategies carried out by street vendors (PKL) in increasing income for family welfare, and what are the obstacles faced by them. This research uses a descriptive qualitative approach. In this study, data analysis techniques such as data reduction, data collection, data presentation, and conclusion drawing are used. Based on the results of the study, it can be concluded that the strategies carried out by street vendors are maintaining product quality, setting appropriate product prices, conducting promotions, selecting strategic locations, and providing the best service to buyers and the obstacles faced by street vendors are business location and capital access